Comparison of two different designs of forefoot off-loader shoes and their influence on gait and spinal posture - Michalik, Roman; Siebers, H.; Classen, T.; Gatz, M.; Rohof, B.; Eschweiler, J.; Quack; Betsch, Marcel (Gait & Posture, 2019)
Background: The purpose of forefoot off-loader shoes (FOS) is to unload the operated region of the foot in order to allow early mobilization and rehabilitation. However, little is known about the actual biomechanical effects of different designs of FOS on gait, pelvis and spine. Research question: Aim of this study was to analyse and compare the effects of two different designs of forefoot unloader shoes. Methods: Ortho-Wedge (FOS A) and Relief-Dual® (FOS B) were evaluated in this study during standing and while walking. Changes of the pelvic position and spinal posture were measured with a surface topography system and an instrumented treadmill. Gait phases were detected automatically by a built-in pressure plate. Results: Both FOS resulted in a significant increase of pelvic obliquity, pelvic torsion, lateral deviation and surface rotation (p < 0.001) while standing. Between both shoe models, pelvic obliquity and lateral deviation (p < 0.05) were significantly different. During walking, both FOS had a significant effect on spine and pelvis (p < 0.05), however only minor differences were found between the designs. All gait parameters were affected more, wearing FOS A than B. Step length were significantly longer by wearing FOS (p < 0.005). However stance phase raised and swing phase is reduced on the leg wearing FOS A (p < 0.001). Significance: The study showed that FOS lead to significant changes in pelvic position and spinal posture during standing and while walking. A compensating shoe on the contralateral side is therefore recommend. Gait parameters however were affected more by the traditional FOS A half-shoe. The sole- design and shape of FOS B leads to a more physiological roll-over of the foot.
CRIS-Team Scopus Importer:2022-07-20
Keywords: Forefoot off-loader shoe; Gait analysis; Leg length inequalities; Orthopaedic shoes; Rasterstereography